Investigating Hydroclimatic Impacts of the 168158BCE Volcanic Quartet and their Relevance to the Nile River Basin and Egyptian History - Ludlow, Francis (My University, 2023)
The Ptolemaic era (305–30 BCE) is an important period of Ancient Egyptian history known for its material and scientific advances, but also intermittent political and social unrest in the form of (sometimes widespread) revolts against the Ptolemaic elites. While the role of environmental pressures has long been overlooked in this period of Egyptian history, ice-core-based volcanic histories have identified the period as experiencing multiple notable eruptions, and a repeated temporal association between explosive volcanism and revolt has recently been noted. Here we analyze the global and regional (Nile River basin) hydroclimatic response to a unique historical sequence of four large and closely timed volcanic eruptions (first a tropical one, followed by three extratropical northern hemispheric events) between 168 and 158 BCE, a particularly troubled period in Ptolemaic history for which we now provide a more detailed hydroclimatic context. The NASA (National Aeronautics and Space Administration) GISS (Goddard Institute for Space Studies) ModelE2.1 Earth system model simulates a strong radiative response with a radiative forcing (top of atmosphere) of −7.5 W m−2 (following the first eruption) and −2.5 W m−2 (after each of the three remaining eruptions) at a global scale. Associated with this, we observe a global surface cooling of the order of 1.5 ∘C following the first (tropical) eruption, with the following three extratropical eruptions extending the cooling period for more than 15 years. Consequently, this series of eruptions is observed to constrain the northward migration of the inter-tropical convergence zone (ITCZ) during the Northern Hemisphere summer monsoon season, and major monsoon zones (African, South Asian, and East Asian) were seen to experience a suppression of rainfall of >1 mm d−1 during the monsoon (JJAS) season averaged for 2 years after each eruption. A substantial suppression of the Indian and North African summer monsoon (over the Nile River headwater region) was seen to strongly affect the modeled river flow in the catchment and discharge at river mouth. River mass flow over the basin was observed to decrease by 29 % and 38 % relative to an unperturbed (non-volcanic) annual mean flow in the first and second year, respectively, after the first (i.e., tropical) eruption. A moderate decrease ranging between 5 % and 18 % was observed after the third and fourth (extratropical) eruptions. These results indicate, in sum, that the first eruption likely produced a strong hydroclimate response, with the following extratropical eruptions prolonging this. These results also support the recently hypothesized association between ice-core-based signals of explosive volcanism and hydroclimatic variability during the Ptolemaic era, including the suppression of the agriculturally critical Nile summer flooding.
PUBLISHED
This work is a modeling effort to investigate the hydroclimatic impacts of a volcanic quartet during 168158BCE over the Nile River basin in the context of Ancient Egypt's Ptolemaic era (30530BCE). The model simulated a robust surface cooling (~1.01.5C), suppressing the African monsoon (deficit of >1mmd1 over East Africa) and agriculturally vital Nile summer flooding. Our result supports the hypothesized relation between volcanic eruptions, hydroclimatic shocks, and societal impacts.
Keywords: Smart & Sustainable Planet; ANCIENT; CLIMATE VARIABILITY AND PREDICTABILITY (CLIVAR); CLIMATE-CHANGE; Egypt; Humanities; ICE CORE; MONSOON; Nile River; PALEOCLIMATE; Ptolemaic Egypt; Volcanology; ancient egypt; ancient history; environmental history; explosive volcanism; Environment and housing; History